Exploring the Influence of Green Transparency on the Purchase Intention of Green Products - GEN LI (Journal of Emerging Trends in Marketing and Management, 2020)
The issue of greenwashing has raised consumers’ suspicion towards green brands and created a negative impact on the authenticity of green brands (Chen and Chang, 2013). There has also been a growing demand for green brand authenticity at a broader level, which has become an essential criteria for choosing green brands (Beverland and Farrelly, 2010; Ewing, Allen and Ewing, 2012). Prior research has explored different dimensions of brand authenticity within different contexts including fashion (Choi et al., 2015) and fast moving consuming goods (FMCG) (Beverland, 2006). Different capacities of brand authenticity including brand extension authenticity (Spiggle, Nguyen and Caravella, 2012), consumer-brand authenticity (Napoli, Dickinson, Beverland and Farrelly, 2014), and service brand authenticity (Daugstad and Kirchengast, 2013) have also been explored. Despite recent development of the prior literature, our understanding of green brand authenticity with regards to consumers’ purchase intention remains limited. This study seeks to gain insights into the puzzle of green brand authenticity and its influence on consumers’ purchase intention. It contributes to the extant body of the literature by providing an authenticity perspective for understanding consumers’ response to green brands. Building on theory of planned behavior, our framework will explore the impact of green brand transparency on the green brand authenticity.